VAT Agents View on the Theory of Planned Behaviour and Penalty Magnitude: Preliminary Findings from Nigeria - Gimba, Hannatu Yohanna; Ibrahim, Idawati (2017)
Objective: This paper investigates the relationship between penalty magnitude, attitude towards VAT compliance, subjective norms and perceived behavioural control on VAT compliance intention among SMEs in Nigeria.Methodology: Data was gathered through administration of 30 questionnaires.The respondents are SMEs in Kano, North-west, Nigeria.A total of 23 indicator items was measured on 5-point Likert Scale from 1 (strongly disagree) to 5 (strongly agree).IBM SPSS Statistics 23 was employed as the primary statistical analysis tool for the study.Results: The result indicates positive significant relationship of penalty magnitude, subjective norms and perceived behavioural control on VAT compliance intention, while attitude towards VAT compliance has no relationship with VAT compliance intention. Implications: This study recommends a blend of economic and socio-psychological factors in dealing with issues concerning VAT compliance among SMEs, as that will encourage the SMEs to remit the VAT collections and also assist the policy makers to map-out policies that would ensure an effective management and tackling the issues surrounding VAT non-compliance among SMEs in Nigeria as well as other developing countries. In addition, further studies on a larger number of respondents should be conducted to test the consistency of the results.